Public baths in Roman Dion (Colonia Iulia Augusta Diensis) - Oulkeroglou, Anastasios (Journal of Greek Archaeology, 2017)
The city of Dion was founded in the NE foothills of mount Olympus next to a traditional religious centre, which evolved into the official religious centre of the Macedonian kingdom. After the turbulent period of the Roman Civil War, Colonia Iulia Augusta Diensis was founded during the reign of Augustus, probably in 30 BC. The city covered an area of ​​approximately 40 hectares (Figure 1). Roman veterans were settled among the indigenous population.